Manajemen Luka Bakar Kornea: Literature Review - I Gusti Ngurah Kezawa Arisurya; I Gusti Putu Okta Santu Prastya; Ketut Ayu Restu Saptrianing Tyas; Putu Indah Budi Apsari (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
Corneal burns are complex eye injuries that require innovative strategies for effective management. Eye burns related to exposure can be categorized into chemical burns (acid and alkali burns), radiation burns from ultraviolet (UV) sources, and thermal burns. Alkaline corneal injuries are more common than acidic due to the prevalence of household cleaning agents containing ammonia and alkali. Acid burns are usually work-related injuries involving industrial processes, but can also be intentional attacks. The clinical manifestations of corneal burns involve several main symptoms that indicate the severity of the injury. Such pain interferes with daily activities and causes significant discomfort, requiring immediate medical attention. Successful management of corneal swelling and injury has been achieved through methods such as Dex-NW, cross-linked hyaluronic acid, antioxidant Tualang honey, sodium hyaluronic acid and topical vitamin c treatment.